Magnetic Resonance Elastography of the Liver in Patients Status – Post Fontan Procedure: Feasibility and Preliminary Results - Serai, Suraj D. (Congenit Heart Dis, 2013)
Objective: The purpose of this study was to evaluate the feasibility of performing MR Elastography (MRE) as a screening tool for elevated liver stiffness in patients’ status-post Fontan procedure. With Fontan patients now reaching adulthood, one of the factors that is increasingly affecting long-term prognosis is the presence of hepatic congestion and fibrosis. When the liver fibrosis progresses to cirrhosis, these patients may be candidates for liver transplantation. However, if detected early, steps can be taken to potentially slow or halt the progression of hepatic fibrosis. Currently, liver biopsy is the gold-standard for assessing liver fibrosis. Magnetic Resonance Elastography (MRE) is a relatively new, non-invasive imaging technique that quantitatively measures liver stiffness and provides an estimate of fibrosis extent. A retrospective study was performed evaluating liver stiffness with MRE in patients with a history of Fontan procedure. The MRE of the liver was performed in the same session as a clinical cardiac MRI. Liver stiffness values were calculated by drawing regions-of-interest on the stiffness maps. The mean liver stiffness and its correlation with the length of time since Fontan surgery were studied. Sixteen patients with 17 MRE exams were included in this study. All patients had elevated liver stiffness values by MRE, suggesting the presence of mild to severe fibrosis, and there was a trend towards higher liver stiffness with greater duration of time with the Fontan circulation. MRE is a feasible method for evaluating the liver in patients status-post Fontan procedure who are undergoing surveillance cardiac MRI. Our preliminary study shows that duration of hepatic congestion following Fontan procedure may be related to liver stiffness. Further investigation with histologic correlation is needed to determine the etiology and long-term sequela of elevated liver stiffness in this population.